Упростите выражения, раскрыть скобки и привести подобные слогаемые:20а-(4в-5с)+(-17а+3в-с)-(2а-2в-16с)x(x+y)-y(x-y)3(x-2y)+2(x-3y)(x+4)(x-2)-(x+2)(x-1)(x^2-2x+5)( x^2+x-3) 

Упростите выражения, раскрыть скобки и привести подобные слогаемые: 20а-(4в-5с)+(-17а+3в-с)-(2а-2в-16с) x(x+y)-y(x-y) 3(x-2y)+2(x-3y) (x+4)(x-2)-(x+2)(x-1) (x^2-2x+5)( x^2+x-3)  
Гость
Ответ(ы) на вопрос:
Гость
20a-(4b-5c)+(-17a+3b-c)-(2a-2b-16c)=20a-4b+5c-17a+3b-c-2a+2b+16c=a+b+20c x(x+y)-y(x-y)=x²+xy-xy+y²=x²+y² 3(x-2y)+3(x-3y)=3x-6y+2x-6y=5x-12y (x+4)(x-2)-(x+2)(x-1)=x²+2x-8-x²-x+2=x-6 (x²-2x+5)(x²+x-3)=x⁴+x³-3x²-2x³-2x²+6x+5x²+5x-15=x⁴-x³+5x-9
Гость
[latex]1)20a-(4b-5c)+(-17a+3b-c)-(2a-2b-16c)=\\ 20a-4b+5c-17a+3b-c-2a+2b+16c=a+b+20c\\ 2)x(x+y)-y(x-y)= x^{2} +xy-xy+y ^{2} = x^{2} +y ^{2} \\ 3)3(x-2y)+2(x-3y)=3x-6y+2x-6y=5x-12y\\ 4)(x+4)(x-2)-(x+2)(x-1)= \\x^{2} +4x-2x-8- x^{2} -2x+x+2=x-6\\ 5)( x^{2} -2x+5)( x^{2} +x-3)= x^{4} + x^{3}-3 x^{2} -2 x^{3} -2 x^{2} +6x+5 x^{2} +5x-15=\\ x^{4} - x^{3} - +11x-15[/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы